A study of the sensory and nutritional quality of virgin olive oil in relation to variety, ripeness and extraction technology. Overview of the three year study and conclusion - Mario Bertuccioli (Grasas y Aceites)
This lecture provides an outline of the main goals achieved during three years of research activity. The results show how to ensure the maximum chance of success by matching consumer's needs and preferences. Information about consumer is obtained through preference tests and may be used in a company to formulate the right product. The key by which the consumer information reach the producers is the sensory profile of the product. A olive oil sensory wheel has been proposed to clarify and improve the list of standardized olive oil flavour descriptors. The order of terms has been organized to facilitate its use. This proposed system represents a powerful tool to facilitate communication among producers and consumers of the international market. Sensory preference, flavour profile testing, and complex statistical procedures for relating olive oil attributes to the preferences represent important improvement in traditional approaches for defining and identifying desirable product attributes. A secondary Flair goal has been to develop a strategy to predict a specific property (i.e. oxidation stability) of olive oil.